2016
DOI: 10.18203/2320-1770.ijrcog20162975
|View full text |Cite
|
Sign up to set email alerts
|

Serum beta human chorionic gonadotropin and lipid profile in early second trimester (14-20 weeks) is a predictor of pregnancy-induced hypertension

Abstract: Pregnancy is the most important period in women"s life but it can be dangerous also. Pregnancy is a physiological state with increased alteration in biochemical and mechanical processes, if there are no pregnancy complications during pregnancy, these changes will reversible soon after delivery. 1 Hypertension and proteinuria are the important complications of pregnancy and are associated with high maternal and perinatal mortality and morbidity. 2 "Berg and colleagues reported that 16%, 3201 of maternal death i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
5
8
0
Order By: Relevance
“…12 Hernandez R et al and Soundararajan P et al reported similar findings. 13,14 In present study we observed that the higher absolute levels of beta HCG strongly correlate with occurrence of gestational hypertension (Table 4). Out of 190 Pregnant women, 25 women who developed gestational hypertension were having higher absolute levels of beta HCG as compared to 165 pregnant women who did not (Mean±SD; 54907±29509 vs 41095±19103; p<0.001).…”
Section: Discussionsupporting
confidence: 62%
“…12 Hernandez R et al and Soundararajan P et al reported similar findings. 13,14 In present study we observed that the higher absolute levels of beta HCG strongly correlate with occurrence of gestational hypertension (Table 4). Out of 190 Pregnant women, 25 women who developed gestational hypertension were having higher absolute levels of beta HCG as compared to 165 pregnant women who did not (Mean±SD; 54907±29509 vs 41095±19103; p<0.001).…”
Section: Discussionsupporting
confidence: 62%
“…Difference between the groups was statistically significant in this study and above mentioned studies. Similar results were also found in studies of Archana S et al, 11 ; Soundararajan P et al 13 ; El Khouly N 14 and Leela KP et al 12 The association of LDL concentration with preeclampsia is biologically plausible. It has been seen that oxidized LDL increased sensitivity to the presser agents and inhibit epithelial dependent vasodilatation .It is found that the lipid fractions increased in pre-eclamptic patients and plasma lipid peroxidase and free radicals were activated.…”
Section: Discussionsupporting
confidence: 84%
“…In present study, total 200 primigravida patients were recruited to assess the predictive value of increased Beta Human Chorionic Gonadotropin plasma concentration in early second trimester (13-20 weeks) in the occurrence of Hypertensive disorders of pregnancy. Mazhari F [3] , Soundararanjan P et al [4] , Muthulakshmi D et al [5] , & Munirah M et al [6] have opted the similar methodology as in the present study.…”
Section: Discussionmentioning
confidence: 99%